Vibrations in the strengthening processing of machinery parts - Дудников, Анатолий Андреевич; Келемеш, Антон Александрович; Канивец, Александр Васильевич; Горбенко, Александр Викторович; Пасюта, Андрей Григорьевич (Technology audit and production reserves, 2015)
In this paper we discuss the problem of the application of vibrations at hardening the surface of items such as the manufacture and restoration of details of agricultural machinery to increase their share. The aim of the study is to improve the wear resistance of parts through the use of technology developed on the basis of vibration hardening of the working surfaces. Analysis of the wear resistance of parts in conventional vibratory and recovery methods to evaluate the operational durability of these parts, and to develop more efficient technology of hardening in their manufacture and restoration. The process of wear of the cutting element disc coulter seeding machines, found the optimal parameters of the vibration treatment, offering enhanced durability of these components. Based on the data developed and implemented in the production process of hardening of cutting elements disc coulters grain drills based on the vibration deformation of the working surfaces. The results can be used in the manufacture of engineering for hardening of manufactured parts. Developed and implemented in the production process using vibration reduction hardening can improve the durability of working bodies seeding machines.